2014
DOI: 10.2741/4193
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-drug conjugates targeting prostate-specific membrane antigen

Abstract: Prostate-specific membrane antigen (PSMA) is an integral, non-shed membrane glycoprotein that is a well-characterized and clinically validated marker of prostate cancer. The expression profile and other biological properties of PSMA make it an attractive target for antibody-drug conjugate (ADC) therapy of prostate cancer, as well as a broad range of other tumors in which PSMA is abundantly expressed within the tumor neovasculature. PSMA-targeted ADCs have been developed using auristatin and maytansinoid drugs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 138 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…The trial, which was initiated based on a high level of PSMA expression observed in the tumor neovasculature of human glioblastoma multiforme (GBM) (Nomura et al, 2014), found no evidence of PSMA-ADC efficacy (Elinzano et al, 2016). Because PSMA is not overexpressed in rodent tumor vessels (Huang et al, 2004), unlike in humans, preclinical studies with the PSMA ADC were limited to tumor cell models wherein only the tumor cells were PSMA-positive (Olson and Israel, 2014). Our work suggests that the GBM trials likely failed due to the selection of an inappropriate warhead, and suggest that PSMA may still be a valid neovascular drug target for GBM and other human tumor types through the re-engineering of a PBD-linked PSMA ADC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial, which was initiated based on a high level of PSMA expression observed in the tumor neovasculature of human glioblastoma multiforme (GBM) (Nomura et al, 2014), found no evidence of PSMA-ADC efficacy (Elinzano et al, 2016). Because PSMA is not overexpressed in rodent tumor vessels (Huang et al, 2004), unlike in humans, preclinical studies with the PSMA ADC were limited to tumor cell models wherein only the tumor cells were PSMA-positive (Olson and Israel, 2014). Our work suggests that the GBM trials likely failed due to the selection of an inappropriate warhead, and suggest that PSMA may still be a valid neovascular drug target for GBM and other human tumor types through the re-engineering of a PBD-linked PSMA ADC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, even though prostate specific membrane antigen (PSMA) overexpression has been detected in tumor vessels of many human cancers and two PSMA-targeting ADCs have undergone extensive clinical testing for prostate cancer (Olson and Israel, 2014), these agents have only been shown to target PSMA-positive prostate tumor cells in vivo. There are several possible explanations for the paucity of validated ADCs targeting tumor vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a bispecific T cell engaging (BiTE) antibody that recognizes both CD3ɛ of the T cell receptor complex and prostate specific membrane antigen (PSMA) is under preclinical evaluation . In addition, an anti‐PSMA monoclonal antibody conjugated to a cytotoxic drug (PSMA‐ADC) is currently in clinical trials . The recent observation that the presence of heregulin can reduce the cytotoxic effect of a HER2‐directed antibody drug conjugate, trastuzumab emtansine (T‐DM1), in HER2‐overexpressing breast cancer cells provides support for strategies to target HER3 …”
Section: Discussionmentioning
confidence: 99%
“…42 In addition, an anti-PSMA monoclonal antibody conjugated to a cytotoxic drug (PSMA-ADC) is currently in clinical trials. 43 The recent observation that the presence of heregulin can reduce the cytotoxic effect of a HER2-directed antibody drug conjugate, trastuzumab emtansine (T-DM1), in HER2overexpressing breast cancer cells provides support for strategies to target HER3. 44 Development of resistance to inhibition of the PI3K/Akt pathway in HER2-overexpressing breast cancer cells is associated with enhanced HER3 expression and phosphorylation and is in part dependent on FOXO transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Aptamers, mAbs, and peptides have been developed for targeted delivery of drugs or imaging agents to PSMA-expressing cells. 8,10,11 A radiolabeled antibody specific to PSMA (mAb 7E11) is routinely used in clinical practice to target PSMA-positive prostate cancer cells (ProstaScint scan) and has thus become an invaluable tool to monitor the extent of disease.…”
mentioning
confidence: 99%